Frailty and Sarcopenia - Onset, Development and Clinical Challenges 2017
DOI: 10.5772/intechopen.68791
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenic Dysphagia as a New Concept

Abstract: Dysphagia (swallowing difficulties) is a serious problem associated with malnutrition, dehydration, aspiration pneumonia, and death. Its well-known causes include stroke, neuromuscular disease, and head and neck cancer, and these affect muscles and sensation during deglutition. In recent years, dysphagia due to sarcopenia (i.e. "sarcopenic dysphagia") has been reported as a new concept. Sarcopenic dysphagia results from low swallowing and general skeletal muscle mass and strength. The characteristic changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 99 publications
(130 reference statements)
0
12
0
1
Order By: Relevance
“…Additionally, decreased lip strength has been suggested to occur due to sarcopenia and to be related to difficulties in eating and drinking (i.e., dysphagia) [117]. Lip force has been associated with hand grip strength and lip pendency has been associated with aging [117,124].…”
Section: Sarcopenia and Oral Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, decreased lip strength has been suggested to occur due to sarcopenia and to be related to difficulties in eating and drinking (i.e., dysphagia) [117]. Lip force has been associated with hand grip strength and lip pendency has been associated with aging [117,124].…”
Section: Sarcopenia and Oral Statusmentioning
confidence: 99%
“…Indeed, since it has been shown that skeletal muscle mass and strength decline may affect both swallowing and general muscle groups, a new condition, called "sarcopenic dysphagia" has been coined [22,124,125]. Swallowing muscles are characterized by a high percentage of type II fibers, which are more easily affected by malnutrition and sarcopenia than type I muscle fibers [22].…”
Section: Sarcopenia and Oral Statusmentioning
confidence: 99%
“…Dysphagia can be a result of behavioral, sensory, or motor problems (or a combination of these) and is common in individuals with neurologic disease and dementia. Also, studies showed that the weakening of skeletal muscle mass (SMM) might be associated with swallowing impairment, and recently this condition is described as sarcopenic dysphagia . Elderly subjects with both sarcopenia and dysphagia may have not only disease‐related dysphagia but also sarcopenic dysphagia.…”
Section: Introductionmentioning
confidence: 99%
“…Also, studies showed that the weakening of skeletal muscle mass (SMM) might be associated with swallowing impairment, and recently this condition is described as sarcopenic dysphagia. 3 Elderly subjects with both sarcopenia and dysphagia may have not only disease-related dysphagia but also sarcopenic dysphagia. The prevalence of swallowing disorders in older individuals ranges from 13% to 38%, and a few studies reported the prevalence of sarcopenic dysphagia to be between 30% and 42.2%.…”
Section: Introductionmentioning
confidence: 99%
“…Los cambios característicos en los músculos para tragar ocurren principalmente en los músculos orales y faríngeos junto con otros factores asociados 29 . Un metaanálisis sobre la neumonía por aspiración en personas mayores frágiles reveló que la disfagia es un factor de riesgo significativo para la neumonía por aspiración 30 .…”
Section: Discussionunclassified